CD26/DPPIV inhibition alters the expression of immune response-related genes in the thymi of NOD mice. (5th May 2016) - Julián, María Teresa; Alonso, Núria; Colobran, Roger; Sánchez, Alex; Miñarro, Antoni; Pujol-Autonell, Irma; Carrascal, Jorge; Rodríguez-Fernández, Silvia; Ampudia, Rosa María; Vives-Pi, Marta; Puig-Domingo, Manel
Abstract: The transmembrane glycoprotein CD26 or dipeptidyl peptidase IV (DPPIV) is a multifunctional protein. In immune system, CD26 plays a role in T-cell function and is also involved in thymic maturation and emigration patterns. In preclinical studies, treatment with DPPIV inhibitors reduces insulitis and delays or even reverses the new -onset of type 1 diabetes (T1D) in non-obese diabetic (NOD) mice. However, the specific mechanisms involved in these effects remain unknown. The aim of the present study was to investigate how DPPIV inhibition modifies the expression of genes in the thymus of NOD mice by microarray analysis. Changes in the gene expression of β-cell autoantigens and Aire in thymic epithelial cells (TECs) were also evaluated by using qRT-PCR. A DPPIV inhibitor, MK626, was orally administered in the diet for 4 and 6 weeks starting at 6–8 weeks of age. Thymic glands from treated and control mice were obtained for each study checkpoint. Thymus transcriptome analysis revealed that 58 genes were significantly over-expressed in MK626-treated mice after 6 weeks of treatment. Changes in gene expression in the thymus were confined mainly to the immune system, including innate immunity, chemotaxis, antigen presentation and immunoregulation. Most of the genes are implicated in central tolerance mechanisms through several pathways. No differences were observed in the expression of Aire and β-cell autoantigens in TECs. In the current study, we demonstrate that treatment with the DPPIV inhibitor MK626 in NOD mice alters the expression of the immune response-related genes in the thymus, especially those related to immunological central tolerance, and may contribute to the prevention of T1D. Highlights: Treatment with DPPIV inhibitors may contribute to the prevention of T1D. Expression of immune –related genes is modified in the thymi of NOD mice by MK626. MK626 treatment increases the expression of genes involved in central tolerance. DPPIV inhibitor treatment does not alter β-cell autoantigens and Aire expression in TECs.